1988
DOI: 10.1002/1097-4679(198805)44:3<326::aid-jclp2270440305>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

DSM-III diagnosis and code types of the diagnostic inventory of personality and symptoms

Abstract: The relationships of high‐point code types of the Diagnostic Inventory of Personality and Symptoms (DIPS) to the Diagnostic and Statistic Manual III of the American Psychiatric Association (DSM‐III) were explored for patients (N = 316) in private mental health settings. Sixteen DIPS code types that relate code types to Axis I diagnoses are presented. The three DIPS personality disorder cluster scales and the eight combinations thereof are presented as well. Five of the personality disorder cluster scale code t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Using probability scales based on Bayesian concepts, the researchers found the DIPS correctly classified 70% of the private psychiatric patients in comparison to DSM-I11 diagnoses. In a study designed to examine the relationship between code types of the DIPS and Axis I and Axis I1 categories of the DSM-111, the DIPS correctly classified 75% of the patients in private hospital settings (Williams et al, 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using probability scales based on Bayesian concepts, the researchers found the DIPS correctly classified 70% of the private psychiatric patients in comparison to DSM-I11 diagnoses. In a study designed to examine the relationship between code types of the DIPS and Axis I and Axis I1 categories of the DSM-111, the DIPS correctly classified 75% of the patients in private hospital settings (Williams et al, 1988).…”
mentioning
confidence: 99%
“…Validity studies of the DIPS indicated the measure's construct validity ) and criterion-related validity Vincent, 1987;Williams et al, 1988). Vincent and Duthie (1986) conducted a factor analytic study to examine the factor structure of the DIPS with psychiatric inpatients as subjects.…”
mentioning
confidence: 99%